The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ymgmr.2020.100634
|View full text |Cite
|
Sign up to set email alerts
|

False positive cases of elevated tetradecenoyl carnitine in newborn mass screening showed significant loss of body weight

Abstract: Very-long-chain acyl-CoA dehydrogenase (VLCAD) deficiency, a condition in which the body is unable to break down long-chain fatty acids properly, is the most common fatty acid oxidation disorder in Japan. Tandem mass spectrometry has been used in newborn screening (NBS), allowing the detection of patients with VLCAD deficiency even before symptoms manifest. However, tandem mass spectrometry has a high false positive rate. We investigated the clinical characteristics of patients with false positive results for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In newborn screening, false positives have been reported in patients, following a loss of body weight and other circumstances of catalysis of fatty acids [ 86 ] and fasting [ 87 ]. Therefore, poor milk supply, poor sucking, and other causes of body weight loss should be reviewed in these situations.…”
Section: Study Of Metabolites In the Diagnosis Of Fatty Acid Oxidation Defectsmentioning
confidence: 99%
“…In newborn screening, false positives have been reported in patients, following a loss of body weight and other circumstances of catalysis of fatty acids [ 86 ] and fasting [ 87 ]. Therefore, poor milk supply, poor sucking, and other causes of body weight loss should be reviewed in these situations.…”
Section: Study Of Metabolites In the Diagnosis Of Fatty Acid Oxidation Defectsmentioning
confidence: 99%
“…The primary marker is elevated C14:1 acylcarnitine (tetradecenoylcarnitine), together with other longchain acylcarnitines and disease-specific acylcarnitines ratios that can be calculated (C14, C14:2, C14:1/C2, C14:1/C16). As previously reported, MS/MS has a high false-positive rate and it is often difficult to differentiate between true positives, heterozygous carriers, and false positives (Spiekerkoetter, 2010;Bo et al, 2020). False positives can also occur due to insufficient breastfeeding, which might cause an elevation of C14:1 and C14:1/C2.…”
Section: Introductionmentioning
confidence: 96%
“…False positives can also occur due to insufficient breastfeeding, which might cause an elevation of C14:1 and C14:1/C2. That’s why it is suggested that in suspected VLCADD, attending doctors should pay attention to body weight changes recorded during newborn body mass screening ( Bo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some newborns with severe body weight loss were diagnosed with VLCADD in the first NBS results. However, they were false positive results, and the elevation of C14:1-carnitine was due to the increased catalytic process of fatty acids [ 24 ]. Also, it was found that the acylcarnitine profile used for VLCADD patients might be interfering with LCADD [ 25 ].…”
Section: Introductionmentioning
confidence: 99%